Assessing trophic status of Suoi Hai Reservoir using Carlson’s Trophic State Index - Nguyen Thuy, Linh; Nguyen Thi Thu, Ha; Nguyen Thien Phuong, Thao; Pham Quang, Vinh (Vietnam Journal of Earth Sciences, 2021)
The water quality of Suoi Hai reservoir, the largest reservoir in Hanoi city, is being threatened by human activities of the surrounding area, as reported by the press. The trophic status of the reservoir is the result of both natural eutrophication and nutrient inputs from anthropogenic sources, particularly the leachate from a lakeside waste treatment plant. This study aims to identify the trophic status of the Suoi Hai reservoir and the changes of water trophic state over space and time. Data of chlorophyll-a concentration, total phosphorus, and Secchi disk depth from 51 sites during three field campaigns in October 2019, August 2020, and March 2021 was used to calculate Carlson’s trophic state index (CTSI). Resultant CTSI (ranged from 60 to 72) allows classifying Suoi Hai reservoir as highly eutrophic water. Its variations in space and time provided evidence for an influence of anthropogenic activities on the reservoir trophic state. Analysis of the trophic state index deviations suggested that total phosphorus is the key factor that influenced the reservoir trophic state. Therefore, managing the anthropogenic nutrient inputs load to the reservoir should be a critical task to control eutrophication in Suoi Hai Reservoir at present.